Learning and Professional Development of the Mathematics Teacher in Research Communities - Fiorentini, Dario (2013)
The aim of this article is to identify, describe and understand the learning and professional development of teachers who participate in research communities. To analyse and interpret the process, we have chosen the case of a mathematics teacher who, throughout her career, participated in two professional and one academic research communities. The analysis is supported by the social theory of learning in communities, although there have been adaptations for professional and research communities and for teachers. We include descriptions of the learning contexts and a narrative analysis based on the teacher’s history of participation and reification in those communities. The results show that as a result of her collaboration with critical partners in academic or professional research communities, the teacher developed professionally and gained a research-oriented attitude, constantly exploring new knowledge and opportunities regarding what is taught and learnt at school. She also, changed the way she worked and interacted with her pupils and dealt with mathematical and didactic knowledge, especially in classes of pupils with learning difficulties.